2021
DOI: 10.3389/fncel.2021.652593
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides: Roles in the Development of Microglial-Mediated Neuroinflammation and Neurodegeneration

Abstract: Microglia are increasingly recognized as vital players in the pathology of a variety of neurodegenerative conditions including Alzheimer’s (AD) and Parkinson’s (PD) disease. While microglia have a protective role in the brain, their dysfunction can lead to neuroinflammation and contributes to disease progression. Also, a growing body of literature highlights the seven phosphoinositides, or PIPs, as key players in the regulation of microglial-mediated neuroinflammation. These small signaling lipids are phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 373 publications
(434 reference statements)
0
11
0
Order By: Relevance
“…Alzheimer's disease (AD) is a degenerative disease of the central nervous system that occurs in old age and pre-old age and is characterized by progressive cognitive dysfunction and behavioral impairment [ 1 , 2 ]. It is the most common type of dementia and one of the most common chronic diseases in old age [ 3 ], accounting for about 50% to 70% of dementia in old age [ 4 , 5 ]. While the exact cause of AD has not been elucidated, studies have found that AD is the result of a combination of genes, lifestyle, and environmental factors, caused in part by specific genetic changes [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a degenerative disease of the central nervous system that occurs in old age and pre-old age and is characterized by progressive cognitive dysfunction and behavioral impairment [ 1 , 2 ]. It is the most common type of dementia and one of the most common chronic diseases in old age [ 3 ], accounting for about 50% to 70% of dementia in old age [ 4 , 5 ]. While the exact cause of AD has not been elucidated, studies have found that AD is the result of a combination of genes, lifestyle, and environmental factors, caused in part by specific genetic changes [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The significance of the finding is underscored by the pivotal role PI45P2 plays in the nervous system, particularly in regulating various facets of the synaptic vesicle cycle. Supporting this, disruptions in phosphoinositides levels and signaling have been identified in numerous dementias 54 . Notably, both Alzheimer's Disease (AD) and Parkinson's Disease (PD) manifest alterations in the expression of phosphoinositide conversion enzymes, pinpointing these enzymes as promising therapeutic targets 55,56 .…”
Section: Enrichment Of Sv Mimetics With Pi45p2 Resulted In Increased ...mentioning
confidence: 77%
“…The relative PI5P4Kα activity of 6 could be increased by methylation of the pyridyl 3-position (10) more effectively than by addition of OMe (11), or F ( 12) at the same position, or by chlorination at the pyridyl 2-position (13; Table 2). A range of small substituents was also trialled on template 6 and these were generally well tolerated (see [14][15][16][17]. Compound 17 was a useful lead from this set with a good balance of activity at PI5P4Kα and γ+ as well as one of the lower X log Ps in this series.…”
Section: Resultsmentioning
confidence: 99%
“…The promiscuity of the phosphoinositides in cellular signalling pathways has implications for disease as enzyme dysfunction or misregulation may be causative in various developmental disorders, inflammation and infection. [13][14][15][16] As oncology targets, PI5P4Ks have become increasingly associated with a number of diseases. 17 Interestingly the involvement of PI5P4Kα alone has been documented in glioblastoma, acute myeloid leukemia (AML) and prostate cancer [18][19][20][21] but other examples suggest that there may be a combinatorial role for the PI5P4Ks.…”
Section: Introductionmentioning
confidence: 99%